Social Justice and Counselling Psychology: Situating the Role of Graduate Student Research, Education, and Training - Palmer, Angèle; Parish, Jessica (Canadian Journal of Counselling and Psychotherapy, 2008)
While social justice advocacy has been a part of counselling psychology since its inception, its role in the field has been debated. Many professionals have called for increased attention to social justice awareness and advocacy to enable the profession to meet the expanding needs of clients. The present article proposes that a move toward prioritizing social-justice issues necessitates the inclusion of graduate students. The authors contend that graduate programming in counselling psychology must provide students with opportunities to engage with the critical discourses of critical psychology, feminism, and multiculturalism in the aim of pursuing social justice-oriented practice and research.